Performance Comparison Analysis Before and After the Acquisition of a National Gas Company - Masno Marjohan (Dinasti Publisher, 2023)
The purpose of this study is to analyze the difference in the financial performance of Perusahaan Gas Negara before and after the acquisition, as measured by financial measures. Financial performance is related to the current Ratio (CR), Quick Ratio (QR), Return on Equity (ROA), Return on Equity (ROE), Debt to Assets Ratio (DAR) Ratio debt to equity (DER). The research method used is descriptive analysis, this study was carried out at the State Gas Company, taking data from the website of the Indonesian Stock Exchange (IDX). The data source used in this study is secondary data in the form of annual financial statements of Perusahaan Gas Negara for the period 2017-2021. This study uses the Wilcoxon rank test of normality as a data analysis technique to determine whether there are significant differences in the financial performance of Perusahaan Gas Negara before and after the acquisition. The results of this study show the financial performance of Perusahaan Gas Negara based on descriptive analysis of financial measures based on the current ratio (CR), quick ratio (QR), quick ratio return on equity (ROA) and return on equity (ROE) decreased while debt to equity ratio (DAR) and debt to equity ratio (DER) both get a raise. In Wilcoxon's signed hypothesis test, where the Asymp-Sig value is 0.760 > the significance value ? = 05, i.e., there is no significant difference in financial performance ratio between Perusahaan Gas Negara before and after the acquisition.